1983
DOI: 10.1177/153944928300300302
|View full text |Cite
|
Sign up to set email alerts
|

Faculty Evaluation Practices among Occupational Therapy Chairpersons: A Comparative Study

Abstract: A perennial question for academic health programs has been: What is the relationship between the faculty evaluation practices of academic health programs and those of general liberal arts programs? The purpose of this study was to compare the faculty evaluation practices of a sample of occupational therapy chairpersons with those of a recent national sample of deans of public and private liberal arts colleges Major areas of inquiry focused on institutional policies and practices in evaluating faculty performan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

1985
1985
2002
2002

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 4 publications
0
2
0
Order By: Relevance
“…However, a recent study by Lanier, Hedl, and Christiansen (1983) found that faculty evaluation practices in these programs may be consistent with a reward system that stresses teaching over research. The 23 OT program chairpersons surveyed were found to be similar to a sample of liberal arts college deans in that they ranked classroom teaching highest as a major factor in evaluating overall faculty performance.…”
Section: Otacademic Reward Systems Do Notplaceas Much Emphasis On Pubmentioning
confidence: 97%
“…However, a recent study by Lanier, Hedl, and Christiansen (1983) found that faculty evaluation practices in these programs may be consistent with a reward system that stresses teaching over research. The 23 OT program chairpersons surveyed were found to be similar to a sample of liberal arts college deans in that they ranked classroom teaching highest as a major factor in evaluating overall faculty performance.…”
Section: Otacademic Reward Systems Do Notplaceas Much Emphasis On Pubmentioning
confidence: 97%
“…Neither publication of refereed articles nor publication of books predicted salary (Holcomb et al, 1989;Parham, 1985a). Additionally, most occupational therapy chairpersons stressed teaching over research in their faculty evaluations (Lanier, Hedl, & Christiansen, 1983).…”
mentioning
confidence: 99%